2000
DOI: 10.1002/1521-186x(200007)21:5<364::aid-bem5>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Biological and morphological effects on the brain after exposure of rats to a 1439 MHz TDMA field

Abstract: We investigated the effects of exposure to a 1439 MHz TDMA (Time Division Multiple Access) field, as used in cellular phones, on the permeability of the blood-brain barrier (BBB), on the morphological changes of the brain, and on body-mass fluctuations. Male Sprague-Dawley (SD) rats were divided into three groups of eight rats each. The rats in the EM(+) group, which had their heads arrayed in a circle near the central antenna of an exposure system, were exposed to a 1439 MHz field for one hour a day. The rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(23 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“…The exposure system design was based on a previous report [Burkhardt et al, 1997], and it was the same as that used in a previous study [Tsurita et al, 2000]. In brief, the system consisted of a small anechoic chamber, a round turntable with eight tubes (28 cm in length, 6 cm in diameter), a monopole antenna on the floor, and a cylinder with a fan on the ceiling to provide fresh air.…”
Section: Exposure Systemmentioning
confidence: 99%
“…The exposure system design was based on a previous report [Burkhardt et al, 1997], and it was the same as that used in a previous study [Tsurita et al, 2000]. In brief, the system consisted of a small anechoic chamber, a round turntable with eight tubes (28 cm in length, 6 cm in diameter), a monopole antenna on the floor, and a cylinder with a fan on the ceiling to provide fresh air.…”
Section: Exposure Systemmentioning
confidence: 99%
“…Therefore, biological effects of RF‐EMF and their consequences on human health are receiving increasing scientific interest and have now become an urgent problem. Hematological , pathological , cardiac , endocrine , reproductive , and nervous changes , and also oxidative stress , cataract , and behavioral alterations due to EMF exposure have been evaluated previously by in vivo and in vitro studies. Some recent studies using newer techniques such as immunohistochemistry have investigated effects of radiation exposure on specific proteins .…”
Section: Introductionmentioning
confidence: 99%
“…A debate is ongoing over the effect of RF EMF exposure on BBB permeability. Numerous studies have reported no changes in BBB permeability after exposure to RF EMF [17], [22], [23]; changes in permeability (if present) have been attributed to an increase in temperature-induced blood flow [17], [20], [24], [25]. However, other studies [19], [26][29] have consistently reported increased BBB permeability after exposure to EMF.…”
Section: Introductionmentioning
confidence: 99%